MISCONCEPTION ANALYSIS OF HEAT EXPANSION AND TEMPERATURE MATERIAL IN CLASS VII JUNIOR HIGH SCHOOL STUDENTS - Athiyyah Romiizah; Dira Luckya Helmi (Pendidikan IPA, FMIPA, UNP, 2023)
This study aims to describe the misconceptions of seventh grade students in science materials, especially temperature, heat, and expansion materials at SMP Negeri 28 Padang. The type of research used in this misconception research is descriptive quantitative. The sample in this study were 29 seventh grade students at SMP Negeri 28 Padang in the 2022/2023 academic year who had learned the concepts of temperature, heat, and expansion. The data collection technique used was a diagnostic test. The data analysis technique in this study consists of several steps, including classifying student answers to determine misconceptions about temperature, heat, and expansion material with a percentage of categories of understanding the concept, not understanding the concept, misconceptions, and guessing. Based on the results obtained, it can be concluded that there are several things that cause misconceptions, which include the lack of student interest in learning because it is influenced by the thought that learning science is difficult, the lack of teacher confirmation regarding concepts that students understand, the learning process that is still teacher-centered, and the absence of a fixed learning resource so that the teacher becomes the most dominant source of information for students.